DUPONT ANALYZES IN THE ASSESSMENT OF BANKING SYSTEM PROFITABILITY: ESTIMATING EVIDENCE FROM THE REPUBLIC OF ARMENIA - Harutyunyan, Gayane (KATCHAR / ACADEMIA. SOCIAL SCIENCE PERIODICAL, 2025)
In recent years banking system worldwide and especially in the Republic of Armenia (RA) is going through many changes. In 11 years period (2014-2024) the banking system of RA went through various challanges: in fact of Equity normative level was increased many banks had to merge and acquire, Covid-19 pandemic led to changes in government policy, in 2020 there was a territorial conflict between Armenia and Azerbaijan which led some banks to change their territorial location. Besides, there were many changes in banking regulation that strengthened the proof in banks and banking regulation and led to continuous rise in profitability. The conducted research aims to discover: what main factors impact the banking system profitability in RA, what factors have the most impact on the latter, whether banking system profitability in RA have potential to rise in the predicted two years. For that purpose DuPont analyzes were performed and five factor analyzes were done to understand which indicators influence the RA banking system profitability the most, to what extent and how. Next, the Trend Lines For three main indicators (ROE, ROS and IB) were constructed to predict the profitability of the banking system for upcoming two years. The analyzes were performed by the tools of prediction in Excel for 2014-2024 data for all the banking system. Analyzed results let us conclude that RA banking system is rapidly growing and ROE changes were driven not only by internal banking indicators but also by changes in legislation in RA.